SMPX Deficiency Causes Stereocilia Degeneration and Progressive Hearing Loss in CBA/CaJ Mice - Tu, Hailong; Zhang, Aizhen; Fu, Xiaolong; Xu, Shiqi; Bai, Xiaohui; Wang, Haibo; Gao, Jiangang (Frontiers in Cell and Developmental Biology, 2021)
The small muscle protein, x-linked (SMPX) encodes a small protein containing 88 amino acids. Malfunction of this protein can cause a sex-linked non-syndromic hearing loss, named X-linked deafness 4 (DFNX4). Herein, we reported a point mutation and a frameshift mutation in two Chinese families who developed gradual hearing loss with age. To explore the impaired sites in the hearing system and the mechanism of DFNX4, we established and validated an Smpx null mouse model using CRISPR-Cas9. By analyzing auditory brainstem response (ABR), male Smpx null mice showed a progressive hearing loss starting from high frequency at the 3rd month. Hearing loss in female mice was milder and occurred later compared to male mice, which was very similar to human beings. Through morphological analyses of mice cochleas, we found the hair cell bundles progressively degenerated from the shortest row. Cellular edema occurred at the end phase of stereocilia degeneration, followed by cell death. By transfecting exogenous fluorescent Smpx into living hair cells, Smpx was observed to be expressed in stereocilia. Through noise exposure, it was shown that Smpx might participate in maintaining hair cell bundles. This Smpx knock-out mouse might be used as a suitable model to explore the pathology of DFNX4.